Optimization of Factors Affecting Iontophoretic Drug Delivery of Diltiazem Hydrochloride Using Factorial Design - Jasmin Jayantilal Garala (Journal of Global Pharma Technology, 2017)
Gel formulation of Diltiazem hydrochloride was prepared using hydroxy propyl methyl cellulose polymer and Dimethyl sulfoxide as a permeation enhancer. Ethanol was added as a co-solvent for proper mixing of Dimethyl sulfoxide in gel. Four factors related to iontophoretic delivery like drug concentration, permeation enhancer concentration, quantity of applied electric current and area of application were optimized using fractional factorial design (24-1). Twelve formulations of Diltiazem hydrochloride gel were prepared and evaluated for in-vitro drug release study using modified diffusion cell. Steady state flux (Jss) for all prepared formulations were calculated as a response and data was evaluated using Design-Expert® software. Based on optimization results final optimized formulation was prepared by using drug concentration of 2.56 % w/w, permeation enhancer concentration of 5% w/w, 0.49 mA current and 1.50cm2 of application area and evaluated for in-vitro iontophoresis using diffusion cell. Steady state flux was found to be 296 μg/h cm2 which was closer to the targeted theoretical Jss (300 μg/h cm2). Desired therapeutic concentration of Diltiazem hydrochloride was achieved by optimizing various factors affecting iontophoretic drug delivery. Iontophoretic drug delivery of Diltiazem hydrochloride using gel formulation is possible. Keywords: Permeation enhancer, Iontophoresis, Factorial design, Steady state flux.